2016
DOI: 10.14740/wjnu277w
|View full text |Cite
|
Sign up to set email alerts
|

Management of Retroperitoneal Schwannoma: Case Reports and Review of the Literature

Abstract: Schwannoma is a rare slow-growing neurogenic tumor of the nerve sheath origin. They are commonly seen in middle-aged with a female to male ratio of 1:1.2. Here we present three cases of retroperitoneal schwannoma in our urology department. In two cases, we decided surgery management and in one case, we used watchful waiting. After a 3-year follow-up, case 1 was asymptomatic without changes in the lesion. Keywords: Schwannoma; Retroperitoneal malignance; Neurogenic tumor IntroductionSchwannoma is a slow-growing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…demonstrating positivity (8). Hirose et al identified GFAP positivity in 92% of their RP cellular/fascicular type schwannomas, which would be consistent with GFAP positivity seen in our cellular type schwannoma.…”
Section: Clinical and Imaging Findingssupporting
confidence: 89%
“…demonstrating positivity (8). Hirose et al identified GFAP positivity in 92% of their RP cellular/fascicular type schwannomas, which would be consistent with GFAP positivity seen in our cellular type schwannoma.…”
Section: Clinical and Imaging Findingssupporting
confidence: 89%
“…CT scan with contrast shows classically a well-defined tumor with slightly low density compared with soft tissue due to the high presence of myelin and fat [ 8 ]. MRI is superior to CT in defining the margins and identifying the nerve origin [ 9 ]. Schwannomas are commonly hypointense on T1 and hyperintense on T2-weighted MR images [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…The target sign (a hypointense center with a hyperintense periphery) and fascicular sign (bundles) are two well-known characteristic features of neurogenic tumors on MRI; however, they are not seen frequently in RSs [ 10 ]. Malignant schwannomas have irregular contours, exhibit mixed intensity on both T1- and T2-weighted images, and tend to invade other structures; however, they are extremely rare in patients without a history of neurofibromatosis [ 9 , 11 ].…”
Section: Discussionmentioning
confidence: 99%